2022
DOI: 10.3390/nu14173657
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19-Related Living Restrictions on Eating Behaviours in Children and Adolescents: A Systematic Review

Abstract: The COVID-19 pandemic prompted the imposition of physical and social distancing measures worldwide. Emerging data suggest that younger age groups may be particularly vulnerable to the adverse mental health impacts of the pandemic. Since the start of the COVID-19 pandemic, there has been an unprecedented increase in demand for child and adolescent eating disorder services. The aim of this review was to systematically review and appraise the current literature on the impact of COVID-19-related living restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
8
1
Order By: Relevance
“…However, this fact does not agree with the results found in this study, since many authors inferred that the pandemic and social isolation brought an increase in the incidence and/or worsening of mental disorders [12], [19], [20], [51]. Do Likewise, [57] argue that children faced problems that directly influenced their mental health like adults.…”
Section: Discussioncontrasting
confidence: 92%
“…However, this fact does not agree with the results found in this study, since many authors inferred that the pandemic and social isolation brought an increase in the incidence and/or worsening of mental disorders [12], [19], [20], [51]. Do Likewise, [57] argue that children faced problems that directly influenced their mental health like adults.…”
Section: Discussioncontrasting
confidence: 92%
“…Previous studies have shown an increase in childhood obesity due to lifestyle changes during the pandemic. 18 A retrospective study conducted in South Korea reported that the percentage of children who had overweight or obesity increased from 24.5% to 38.1% during the COVID-19 pandemic lockdown within 1 year. 19 Similarly, in Australia, the percentage of children with overweight or obesity aged 7-10 years increased from 20.7% in September 2019 to 26.2% in March 2021.…”
Section: Trends In Physical Fitness Test Results and Exercise Timementioning
confidence: 99%
“…In 2020, the COVID‐19 pandemic occurred, and cities were locked down globally. Previous studies have shown an increase in childhood obesity due to lifestyle changes during the pandemic 18 . A retrospective study conducted in South Korea reported that the percentage of children who had overweight or obesity increased from 24.5% to 38.1% during the COVID‐19 pandemic lockdown within 1 year 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to pool the data into a statistical meta-analysis also due to the imprecision of the estimates; therefore, we conducted a narrative synthesis with a summary of the findings (a synthesis without meta-analysis; SWiM) [ 24 ]. We presented the strength of evidence of outcomes with the statistically significant results ( p < 0.05) and calculated Cohen’s d effect sizes for statistically significant outcomes, where means and standard deviations were available and marked them as trivial (effect size greater than 0 and lower than 0.2), small (effect size greater than or equal to 0.2), medium (effect size greater than or equal to 0.5) or large (effect size and greater than or equal to 0.8) [ 25 , 26 ]. We also assessed the certainty of the evidence according to the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) using the GRADEpro GDT tool considering the following domains: risk of bias, inconsistency, indirectness, imprecision and overall certainty level.…”
Section: Methodsmentioning
confidence: 99%